A study to assess the knowledge and attitude of parents of children with epilepsy - Manju, V M; Joshi, Poonam; Gulati, Shefali (Indian Journal of Child Health, 2015)
Objective: The objective was to evaluate the knowledge and attitude of parents of children with epilepsy toward the disease. Methods: In this cross-sectional, descriptive study, parents of 60 children with epilepsy from pediatric neurology clinic of All India Institute of Medical Sciences were enrolled. Data on epilepsy were collected using pre-tested and validated self-developed knowledge, belief, and attitude questionnaire (?=0.85, 0.89). Results: The mean knowledge and attitude scores of parents of the children with epilepsy were 9.82±3.9 (2-22) and 31.25±9.27 (0-40), respectively. Parents of the children with epilepsy had poor 50 (83.3%, scores <60%) to fair knowledge scores (60-70%). Majority of the parents 33 (55%) had excellent attitude (?80%), while 11 (18.3%), 6 (10%), and 10 (16.7%) parents had good, fair, and poor attitude, respectively. Correlation between knowledge and attitude was found to be very weak and negative (r=?0. 039, p=0.77) with few misconception related to disease and clear idea about the activities to be performed with/without caution. Conclusion: There is a need for developing informational booklet and conducting educational sessions on epilepsy for the parents in particular and public in general.